Comparative genomic analysis provides insights into the evolution and niche adaptation of marine M agnetospira sp. QH ‐2 strain - Boyang Ji; Sheng‐Da Zhang; Pascal Arnoux; Zoe Rouy; François Alberto; Nadège Philippe; Dorothée Murat; Wei‐Jia Zhang; Jean‐Baptiste Rioux; Nicolas Ginet; Monique Sabaty; Sophie Mangenot; et al. (Environmental Microbiology, 2014)
Summary Magnetotactic bacteria ( MTB ) are capable of synthesizing intracellular organelles, the magnetosomes, that are membrane‐bounded magnetite or greigite crystals arranged in chains. Although MTB are widely spread in various ecosystems, few axenic cultures are available, and only freshwater M agnetospirillum spp. have been genetically analysed. Here, we present the complete genome sequence of a marine magnetotactic spirillum, M agnetospira sp. QH ‐2. The high number of repeats and transposable elements account for the differences in QH ‐2 genome structure compared with other relatives. Gene cluster synteny and gene correlation analyses indicate that the insertion of the magnetosome island in the QH ‐2 genome occurred after divergence between freshwater and marine magnetospirilla. The presence of a sodium‐quinone reductase, sodium transporters and other functional genes are evidence of the adaptive evolution of M agnetospira sp. QH ‐2 to the marine ecosystem. Genes well conserved among freshwater magnetospirilla for nitrogen fixation and assimilatory nitrate respiration are absent from the QH ‐2 genome. Unlike freshwater M agnetospirillum spp., marine M agnetospira sp. QH ‐2 neither has TonB and TonB ‐dependent receptors nor does it grow on trace amounts of iron. Taken together, our results show a distinct, adaptive evolution of M agnetospira sp. QH ‐2 to marine sediments in comparison with its closely related freshwater counterparts.